DEVELOPMENT OF STUDENTS' DIGITAL COMPETENCE IN THE PROCESS OF INDEPENDENT STUDY - Khanbabayev Khakimzhan Ikramovich (Galaxy International Interdisciplinary Research Journal, 2023)
Improving independent learning activities to develop digital competencies in students allows them to take ownership of their education and develop their digital skills. Some strategies for enhancing independent learning activities to develop digital competence: